IMPACT OF COVID-19 ON EDUCATION OF UNDERGRADUATE MEDICAL STUDENTS OF PAKISTAN. - Nauman Aziz; Muhammad Waseem; Anmol Fatima; Aqsa Anwar; Fahad Khalid; Taimoor Asghar (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: COVID-19 has caused unrest among medical students all over the world including Pakistan. The objective of this study was to assess the impact of COVID-19 on education of undergraduate medical students of Pakistan by assessing their responses to a survey. METHODOLOGY: A validated questionnaire of this cross-sectional analytical study was distributed among 900 undergraduate MBBS students of different medical colleges and universities across Pakistan. Results were assessed by using SPSS version-24. RESULTS: The response rate of our study was 85%. Majority of the participants were females (64.4%) while the fourth year MBBS students took part in the survey with the highest number of students, 434 (56.7%). Major part of the participants (90.8%) agreed to the fact that COVID-19 has affected their study duration. Ninety six percent of the students had online classes during this COVID-19 but more than half of the students (52.8%) were of the view that it’s hardly effective. Interestingly 91.5% of the students participating in the survey showed that they have lost interest in studies. A great difficulty was faced by the students in establishing boundaries between work and home (84.0%). Almost eighty five percent of the students missed their classroom environments. CONCLUSION: There is a huge impact of COVID-19 on medical education of the students in Pakistan. It affected them both physically and mentally and created great phobia in them related to future of their education.